Epidemiology of rare cancers and inequalities in oncologic outcomes. Issue 1 (January 2019) - ,; Hackl, Monika; Eycken, Elizabeth Van; Henau, Kris; Dimitrova, Nadya; Sekerija, Mario; Dušek, Ladislav; Mägi, Margit; Malila, Nea; Leinonen, Maarit; Velten, Michel; Troussard, Xavier; et al.
Abstract: Rare cancers epidemiology is better known compared to the other rare diseases. Thanks to the long history of the European population-based cancer registries and to the EUROCARE huge database, the burden of rare cancers has been estimated the European (EU28) population. A considerable fraction of all cancers is represented by rare cancers (24%). They are a heterogeneous group of diseases, but they share similar problems: uncertainty of diagnosis, lack of therapies, poor research opportunities, difficulties in clinical trials, lack of expertise and of centres of reference. This paper analyses the major epidemiological indicators of frequency (incidence and prevalence) and outcome (5-year survival) of all rare cancers combined and of selected rare cancers that will be in depth treated in this monographic issue. Source of the results is the RARECAREnet search tool, a database publicly available. Disparities both in incidence and survival, and consequently in prevalence of rare cancers were reported across European countries. Major differences were shown in outcome: 5-year relative survival for all rare cancers together, adjusted by age and case-mix, varied from 55% or more (Italy, Germany, Belgium and Iceland) and less than 40% (Bulgaria, Lithuania and Slovakia) . Similarly, for all the analyzed rare cancers, a large survival gap was observed between the Eastern and the Nordic and Central European regions. Dramatic geographical variations were assessed for curable cancers like testicular and non epithelial ovarian cancers. Geographical difference in the annual age-adjusted incidence rates for all rare cancers together varied between >140 per 100, 000 (Italy, Scotland, France, Germany, and Switzerland) and <100 (Finland, Portugal, Malta, and Poland). Prevalence, the major indicator of public health resources needs, was about 7–8 times larger than incidence. Most of rare cancers require complex surgical treatment, thus a multidisciplinary approach is essential and treatment should be provided in centres of expertise and/or in networks including expert centres. Networking is the most appropriate answer to the issues pertaining to rare cancers. Actually, in Europe, an opportunity to improve outcome and reduce disparities is provided by the creation of the European Reference Networks for rare diseases (ERNs). The Joint Action of rare cancers (JARC) is a major European initiative aimed to support the mission of the ERNs. The role of population based cancer registries still remains crucial to describe rare cancers management and outcome in the real word and to evaluate progresses made at the country and at the European level.